2012
DOI: 10.1371/journal.pone.0039484
|View full text |Cite
|
Sign up to set email alerts
|

An Intense and Short-Lasting Burst of Neutrophil Activation Differentiates Early Acute Myocardial Infarction from Systemic Inflammatory Syndromes

Abstract: BackgroundNeutrophils are involved in thrombus formation. We investigated whether specific features of neutrophil activation characterize patients with acute coronary syndromes (ACS) compared to stable angina and to systemic inflammatory diseases.Methods and FindingsThe myeloperoxidase (MPO) content of circulating neutrophils was determined by flow cytometry in 330 subjects: 69 consecutive patients with acute coronary syndromes (ACS), 69 with chronic stable angina (CSA), 50 with inflammation due to either non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
65
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 40 publications
3
65
0
1
Order By: Relevance
“…This observation is in keeping with the observed higher thromboxane A 2 levels produced upon platelet activation, which were associated with high MPO in our study. This observation is in agreement with recent findings that suggested that MPO release is the culprit lesion in STEMI [25], along with the interplay between neutrophils, platelets, and monocytes as aggregates in STEMI [26], and the short, intense burst of neutrophil activation that differentiates early acute myocardial infarction from other systemic inflammatory conditions [27]. Finally, MPO-rich thrombi and high MPO plasma levels have been associated with erythrocyte-rich thrombi, worse reperfusion and left ventricle remodeling in STEMI [28].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This observation is in keeping with the observed higher thromboxane A 2 levels produced upon platelet activation, which were associated with high MPO in our study. This observation is in agreement with recent findings that suggested that MPO release is the culprit lesion in STEMI [25], along with the interplay between neutrophils, platelets, and monocytes as aggregates in STEMI [26], and the short, intense burst of neutrophil activation that differentiates early acute myocardial infarction from other systemic inflammatory conditions [27]. Finally, MPO-rich thrombi and high MPO plasma levels have been associated with erythrocyte-rich thrombi, worse reperfusion and left ventricle remodeling in STEMI [28].…”
Section: Discussionsupporting
confidence: 92%
“…However, a recent study showed that neutrophil activation as assessed by MPO neutrophil content reduction is not observed after septal alcohol ablation, and may be present even with low troponin I levels, suggesting that MPO is less dependent on necrosis than CRP [27]. Therefore, high levels of MPO with low levels of CRP might be utilized as a marker of the formation of early thrombi, which are rich in platelets and neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies report that this activation is induced by platelet-P selectin interactions inducing complete myeloperoxidase depletion in neutrophils. 47 Furthermore, in vitro studies revealed that platelets control the recruitment, activation, differentiation, and cytokine production of different CD4 + T-cell subsets. 48 We recently showed in vivo that platelet CD40L mediates the reduction of circulating Treg cells, thereby promoting the development of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Низька активність МПО в цих клітинах асоціюється з активацією тромбоци-тів і утворенням тромбоцитарно-нейтрофиль-них агрегатів [15,23]. У більшості пацієнтів вміст МПО в плазмі крові хворих на гострий інфаркт міокарда був високим і становив 606,0±59,3 нг/мл (31,9-1870,0 нг/мл).…”
Section: результати та їх обговоренняunclassified